Nepal’s Relationship with India and China in the Changing Context - Nepal, Dilip (Mangal Research Journal, 2021)
Nepal cherishes aged old relationship with India and China. The geo-physical proximity, socio-cultural resemblances in many instances, economy and trade bound historical linkages are few among many aspects, on backdrop of which Nepal has sustained a bilateral and trilateral relationship with India and China. Nevertheless, in course of time, the historical dynamism of relation has changed. This article, in this context, attempts to assess the present day changed dynamics of relationship among Nepal, India and China. It attempts to explore the emergence areas of priorities that have brought trilateral relationship into a newer avenue. I have purposively used a few source books relating to foreign policy of Nepal and Nepal, India, and China relationship to collect data and conceive ideas on trends of relationship development among these three nations. I have applied descriptive research design and attempted to analyze the observed events and incidents in the relationship among these three nations and present it in an understandable manner. The study overall revealed that the economic rise of India and China has brought myriad opportunities to Nepal. However, the emergence of these two immediate neighbors as regional rival and as pursuant of two different ideological interests has higher prospect to grit Nepal’s national interest, and entangle it into a grave tension if it fails to maintain a balance relationship with both the nations. To Nepal, it is a high time to safeguard its national interest and refrain herself from being under the influence of either of the nations as its card.